Response of Peanut Varieties to Phosphorus and Rhizobium Inoculant Rates on Haplic Lixisols of Guinea Savanna Zone of Ghana - Naabe Yaro, Richard; Rufai Mahama, Ahmed; Kugbe, Joseph Xorse; Berdjour, Albert (Frontiers in Sustainable Food Systems, 2021)
Peanut forms a major component of the predominantly cereal-based farming systems in Northern Ghana. However, yields are low, prompting the need to evaluate the effects of phosphorus (PR) and rhizobium inoculant (IR) rates on growth, nodulation, and yield of peanut varieties. On-station and on-farm experiments were conducted to determine the interaction effects of three P rates (0, 30, and 60 kg P2O5/ha), three IR rates (0, 3, and 6 g/kg seed), and two peanut varieties [Chinese and Nkatie Savannah Agricultural Research Institute (SARI)] on growth, nodulation, and yield of peanut on Haplic Lixisols of Northern Ghana. Both experiments were conducted using a split-split plot design replicated three times for the on-station experiment and on six farmer's fields (on-farm experiment). In both experiments, combined application of 60 kg P2O5/ha and IR at 6 g/kg seed increased pod number in the Nkatie SARI and Chinese varieties compared to their control counterparts. PR × V interaction influenced growth, effective nodule number, and podding capacity with 60 kg P2O5/ha combined with Nkatie SARI to produce significantly higher values. The interaction of IR × V improved pod number, nodule number, and harvest index, such that inoculant at 6 g/kg seed combined with Nkatie SARI gave the best performance. PR × IR also had a significant interactive influence on peanut grain yield. Higher grain yields were recorded from 60 kg P2O5/ha in combination with 6 g/kg seed of rhizobium inoculant. Therefore, these results suggest that the use of P fertilizer at 60 kg/ha and rhizobium inoculant at 6 g/kg seed increase peanut productivity on Haplic Lixisols in Northern Ghana. However, it was prudent not to suggest any recommendations from the P rates in interaction with IR, since the result between the on-station and on-farm experiments appeared not consistent.